PUBLIC MANAGEMENT OF REGIONAL DEVELOPMENT BASED ON THE CONCEPT OF SMART SPECIALIZATION IN UKRAINE - Popadynets, Nazariy; Tymkovych, Oksana; Hrafska, Oryslava (Public Management and Policy, 2025)
In the current context of intensifying global competition, structural economic transformations and growing regional disparities, there is a pressing need to introduce new approaches to public management of regional development that can ensure innovative growth and long-term competitiveness of territories. In this context, the concept of smart specialisation is of particular importance as a place-based policy tool that focuses on identifying the unique competitive advantages of regions, activating entrepreneurial potential and concentrating resources on priority areas of development. The purpose of the article is to substantiate the theoretical foundations and practical mechanisms of public management of regional development based on the concept of smart specialisation in Ukraine, taking into account European integration processes and the challenges of post-war recovery. The study uses institutional, systemic and strategic approaches, as well as documentary and comparative analysis methods. The regulatory and legal framework, management practices and results of the implementation of smart specialisation strategies in the regions of Ukraine are analysed. An actor–process–outcome management model is proposed, which allows for the systematisation of the interaction between public administration actors, management processes and the results of the implementation of relevant policies. Key institutional barriers have been identified, in particular the fragmentation of legal regulation, the limited institutional capacity of regional authorities and the formalised nature of the entrepreneurial start-up process. It is concluded that the effectiveness of smart specialisation in Ukraine largely depends on the quality of public administration, the level of inter-level coordination and the development of institutional capacity in the regions. The need to institutionalise smart specialisation at the legislative level, strengthen analytical and management mechanisms, and integrate this approach into the policy of post-war regional recovery is substantiated.